Negative workplace gossip and turnover intention among kindergarten teachers: psychological safety as a mediator and organizational identification as a moderator - Feng, Baoan; Dou, Gaojie; Zhan, Xiaoqian (Frontiers in Psychology, 2025)
PurposeEmpirical evidence examining factors influencing turnover intention among early childhood educators remains scarce, especially research on negative workplace gossip as the influencing factor. To address these shortcomings, this study empirically analyzed whether and how negative workplace gossip, psychological safety, and organizational identification affect kindergarten teachers' turnover intention based on the Chinese cultural background.MethodsA cross-sectional research design was adopted. Self-reported questionnaire data were randomly collected from 1,872 Chinese kindergarten teachers through an online platform. The questionnaire included perceived negative workplace gossip scale, psychological safety scale, organizational identification scale, intent to leave scale, and demographic variables. A moderated mediation model linking negative workplace gossip, psychological safety, organizational identification, and turnover intention was tested using these data.ResultsThe study found that there was an association between negative workplace gossip and the turnover intention of kindergarten teachers. Psychological safety played a mediating role in this relationship, that is, negative workplace gossip influenced teachers' turnover intention by reducing their psychological safety. Meanwhile, organizational identification moderated the relationship between psychological safety and turnover intention. A higher level of organizational identification could weaken the negative impact of psychological safety on turnover intention.ConclusionsKindergarten principals should take various measures to prevent the disorderly development of negative workplace gossip and enhance the psychological safety and organizational identification of kindergarten teachers, which are crucial for reducing the turnover intention of kindergarten teachers.